STRATEGI BELAJAR MENGAJAR DI UPTD SD NEGERI KENARILANG - Orlando De Rois Lapuilana; Yessy Mata (JIP: Jurnal Ilmu Pendidikan, 2026)
This study aims to identify teaching and learning strategies in the world of education. Various teaching methods are used, and their use must be adapted to various factors, such as the situation and conditions under which the teaching and learning activities are taking place, the facilities available, and so on, all of which must be aligned with the educational objectives being achieved. This study aims to determine the learning strategies that teachers and students must employ to achieve learning objectives effectively and efficiently. Data collection methods include observation, interviews, and documentation. Teachers naturally want to continually improve themselves, improve the quality of learning, and deliver teaching materials to students in a way that is easily understood. Furthermore, teachers want to make the teaching process functional. This means a teacher must master teaching methods in specific didactics, which include several theories about teaching methods. Even simple subject matter can sometimes be difficult for students to develop and understand due to inappropriate methods or approaches. Conversely, difficult subjects are easily understood by students because the delivery and methods used are easy to understand, precise, and engaging.